Using OmicsNet for Network Integration and 3D Visualization. Issue 1 (17th December 2018) - Zhou, Guangyan; Xia, Jianguo
Abstract: OmicsNet is a novel web‐based tool for creating and visualizing complex biological networks in 3D space. By coupling a comprehensive knowledgebase with the powerful WebGL technology, OmicsNet allows researchers to intuitively explore molecular interactions and regulatory relationships among genes, transcription factors, microRNAs, and metabolites. OmicsNet fills an important gap by facilitating multi‐omics integration and systems biology. This article contains three basic protocols covering the key features of OmicsNet, including how to create biological networks from a single or multiple list(s) of molecules, how to integrate or enrich different types of networks, and how to navigate the 3D visualization system to obtain biological insights. The OmicsNet web server is freely available at https://www.omicsnet.ca . © 2018 by John Wiley & Sons, Inc.